Cyclodextrin-modified micellar electrokinetic chromatography for the enantioseparation of imidazole and vinpocetini drugs [electronic resource] - Siti Munirah Abd. Wahib, 1984- (2012)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2012